Relevansi Ajaran Kepemimpinan Asta Brata Pada Masa Pandemi Covid-19 - I Made Bagus Andi Purnomo (Kamaya: Jurnal Ilmu Agama, 2021)
The Covid-19 pandemic has a significant impact on various sectors of life. As for some of the impacts, namely on the health, economy, education, culture and environment sectors. The extraordinary impact of the pandemic requires a leader who has an almost perfect leadership spirit so that he can continue to provide welfare to the community. One of the most well-known Hindu leadership styles is Asta Brata's leadership. There are various studies that have examined the implementation of asta brata leadership. However, no one has yet grasped the relevance of asta brata leadership in the covid-19 pandemic. The aims and objectives of this study are to describe the relevance of each of Asta Brata's teachings in today's modern era and to elaborate on the relevance of Asta Brata's teachings during the Covid-19 Pandemic in Buleleng Regency. This research is a qualitative research (qualitative research) using content analysis or content analysis. Research is also supported by literature (library research), which is a type of research that limits its activities only to library collection materials with a combination of phenomenological data that occurs in the field (Buleleng Regency). The results of this study indicate that the teachings of Asta Brata, namely the eight leadership styles that are in accordance with Hindu teachings, are still very relevant to be applied in today's modern era. The eight leadership styles are Indra Brata, Bayu Brata, Kuwera Brata, Agni Brata, Baruna Brata, Yama Brata, Candra Brata and Surya Brata. This leadership pattern is reflected in the antecedents of transformational leadership which is able to realize a shared vision that has been planned and wants to be achieved. As for the relevance of Asta Brata's leadership during the Covid-19 pandemic in Buleleng Regency, namely the relevance of Yama, Kuwera and Agni Brata in the corruption case for national economic recovery (PEN), the relevance of the teachings of Bayu, Baruna and Candra Brata regarding the covid-19 vaccination program and the relevance of Surya Brata. related to the addition of the vaccine quota in Buleleng Regency.